KAPASITAS DAYA DUKUNG JARINGAN PIPA AIR BERSIH DAN VEN GEDUNG LEMBAGA PENGEMBANGAN DAN PENJAMINAN MUTU PENDIDIKAN UNIVERSITAS NEGERI YOGYAKARTA - Adhimas Praditya Kurniawan, Sudiyono (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2014)
ABSTRACTThis last project aims to determine the size and dimensions of the clean water pipelines andventing pipes that will be used in capacity support capability of clean water pipelines andventing pipes in the building of Development and Quality Assurance of Education Institutionsof the Yogyakarta State University. This last project uses calculation method of the amount ofplumbing that based on building data to determine the capacity support capability of the pipeand the discharge flowing in pipelines. Pipe dimension that will be used is determined fromhead loss by using Peter Burberry’s nomogram. This last project is taken from the building ofDevelopment and Quality Assurance of Education Institutions of the Yogyakarta StateUniversity. Stage of this last project includes calculation plumbing load, water flow ratecalculation, head available calculation, calculation of head loss and pipe dimensions. Resultsof this last project are discharge flowing on capacity support capability of clean waterpipelines for 1st pipeline that flowing in 4th west floor building until 1st west floor is 18.28 l/s.In 2nd pipeline, discharge flowing in 3rd east floor until 1st east floor is 11.93 l/s. For 3rdpipeline, discharge flowing in 4th east floor is 5.83 l/d. The diameter that be used in clearwater pipelines in the building of Development and Quality Assurance of Education Institutionsof the Yogyakarta State University are ½”, ¾”, 1”, 1¼”, 1½”, 2”, 2½”, 3”, 4”, and 5”. For ventpipelines are 1½”, 2”, 2½”, 3”, and 4” all of them are qualifying.Keyword: Capacity Support Capability, Clean Water, Vent